Sorting out Aeginetia (Orobanchaceae) in Indochina: A. sessilis is a synonym of A. acaulis - Nuraliev, Maxim S.; Pham, van The; Nguyen, van Canh; Parnell, John A.n. (Phytotaxa, 2023)
Morphological variability of the widespread Aeginetia acaulis is reassessed in the context of the taxonomic boundaries of this species. Aeginetia sessilis considered to be endemic to the Western Ghats of India is demonstrated to lack any clear structural differences from A. acaulis, representing a morph of the latter species with shortly pedicellate (to subsessile or sessile) flowers. Accordingly, A. sessilis is here proved to be a taxonomic synonym of A. acaulis. A population of the same morph is reported from Dak Nong province of Vietnam. Structural diversity of A. acaulis is illustrated with analytical photographs of living plants. Species diversity of Aeginetia in the countries of the Indochinese Peninsula (Cambodia, Laos, Thailand and Vietnam) is summarized, and an identification key is provided. Finally, typification of A. acaulis and its synonym A. abbreviata is revised, and lectotypes are designated for both names.